The Black box : writing the race - Gates, Henry Louis, Jr (Penguin Press, 2024)
"A magnificent, foundational reckoning with how Black Americans have used the written word to define and redefine themselves, in resistance to the lies of racism and often in heated disagreement with each other, over the course of the country's history. Distilled over many years from Henry Louis Gates, Jr.'s legendary Harvard introductory course in African American Studies, The Black Box: Writing the Race, is the story of Black self-definition in America through the prism of the writers who have led the way. From Phillis Wheatley and Frederick Douglass, W.E.B. Du Bois and Booker T. Washington, to Zora Neale Hurston and Richard Wright, James Baldwin and Toni Morrison--these writers used words to create a livable world--a "home"--for Black people destined to live out their lives in a bitterly racist society. It is a book grounded in the beautiful irony that a community formed legally and conceptually by its oppressors to justify brutal sub-human bondage, transformed itself through the word into a community whose foundational definition was based on overcoming one of history's most pernicious lies. This collective act of resistance and transcendence is at the heart of its self-definition as a "community." Out of that contested ground has flowered a resilient, creative, powerful, diverse culture formed by people who have often disagreed markedly about what it means to be "Black," and about how best to shape a usable past out of the materials at hand to call into being a more just and equitable future. This is the epic story of how, through essays and speeches, novels, plays, and poems, a long line of creative thinkers has unveiled the contours of--and resisted confinement in--the "black box" inside which this "nation within a nation" has been assigned, willy nilly, from the nation's founding through to today. This is a book that records the compelling saga of the creation of a people"--